Suicide literacy among first year undergraduate healthcare students in Universiti Sains Malaysia - Sahar, Siti Ainul Farhana (2021)
BACKGROUND Suicide has become a formidable challenge to the mental health practice as the warning signs could manifest subtly or they could be instantaneous. Suicide literacy is a recognised approach to prevent suicide, which involves improving the identification and treatment of individuals at high risk. This study aims to examine the level of suicide literacy among first year healthcare student in Universiti Sains Malaysia (USM) and its predictors. METHODOLOGY A cross-sectional study was conducted among 246 first year undergraduate healthcare students in USM health campus, which is situated in West Malaysia. They were campus students in USM who were recruited via convenient sampling. They were required to complete a set of self-administered questionnaires which include sociodemographic profile, Literacy of Suicide Scale (LOSS) and Depression Literacy (D-Lit). Data was analysed using IBM SPSS Statistical Software Version 24. RESULT The study has found above-average score of suicide literacy 4.9(1.33). There is a positive linear correlation between total D-Lit and LOSS score (p=0.002, r=0.197). Multiple regression analysis showed a significant association between LOSS score and D-Lit score (p=0.012) and courses enrolled by the students (p=0.046), where medical students were found to have a higher level of suicide literacy compared to paramedical students. CONCLUSION There is above-average level of suicide literacy among first year undergraduate healthcare students. It was associated with the courses enrolled by the students and depression literacy. There is a need to enhance the knowledge about suicide and depression among the students, particularly among the paramedical students through continuous psychoeducation and direct involvement in mental health service as part of the gatekeeper training.